IDENTIFICATION AND MAPPING OF THE RELATIONSHIPS BETWEEN CRITERIA IN DECISION-MAKING FOR THE SELECTION OF UNMANNED AERIAL VEHICLES USING THE DEMATEL METHOD - Nurdiansyah, Ervin; Ciptomulyono, Udisubakti; Sutrisno, Sutrisno; Kusdiana, Wawan (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2023)
Decision-making is the process of selecting from several alternatives. Decision-making in selecting an alternative is a series of long processes, starting with identifying problems, seeking information about the alternatives to be selected, and analyzing how good each alternative is, leading to alternative decisions to be made. At the stage of identifying the criteria of an alternative, it is not only about identifying these criteria but also knowing the interrelationships between the criteria of the alternative to be selected. The DEMATEL method is one of the methods in multi-criteria decision-making that can be used to identify the interrelationships between criteria. In this study, calculations were carried out using the DEMATEL method to identify twenty criteria used in the selection of unmanned aircraft. From the results of this study, the DEMATEL method was able to identify and describe the relationship between the criteria quantitatively in the form of a table of the number of relationships and an impact-digraph map. The results of this study indicate that of the twenty criteria, four of the most influential criteria were obtained in the decision-making process for selecting an unmanned aircraft, with the payload criteria being the most influential criterion with the largest value of 0.412, followed by the political criteria in second place with a value of 0.356, while the endurance criteria and range are in third and fourth place on the four criteria that most influence the decision-making process for selecting an unmanned aircraft with a value of 0.355 and 0.341, respectively. Keywords: Decision Making, MCDM, UAV, and DEMATEL